Answer:
f(x) + g(x) = 3x - 2 + 2x + 1
(f + g)(x) = 5x - 1
Answer:I think it's -23.72
Step-by-step explanation:Step 1: Reduce the fraction
Step 2: Multiply
Step 3: Calculate
step 4: solution
Hello from MrBillDoesMath!
Answer:
The first choice ( -12, 20)
Discussion:
Using matrix multiplication we find the equations:
1x + 1y = 8 (A)
2x + 3y = 36 (B)
Next, compute
2(A) - B =>
(2x + 2y) - (2x + 3y) = 2*8 - 36 =>
(2x - 2x) + ( 2y-3y) = 16 - 36 =>
-y = -20 =>
y = 20
Substituting this y value in (A) gives
x + 20 = 8 =>
x = 8 - 20 =>
x = -12
The answer is the first choice ( -12, 20)
Thank you,
MrB
Answer:
One,,,,,,,,,,,,,,,,,,,,,,
The quotient of -3/8 and -1/3 is 1 1/8.